Implementasi Metode MABAC dalam Sistem Pendukung Keputusan Penentuan Lokasi Instalasi WI-FI Publik Oleh Dinas KominfoStan Kabupaten Deli Serdang - Indini, Dwina Pri; Reinaldi, M (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2022)
The need for public Wi-Fi installations is increasing with the aim of being able to meet the needs of the community in accessing the internet for free in public places. Thus, the Deli Serdang Regency Government through the Deli Serdang Regency KominfoStan Service installs a public Wi-Fi network with a limited budget every year. In determining the location of the public Wi-Fi installation, there are many public places, so that the Ministry of Communication and Information Technology is hesitant to determine the right location for the installation of public Wi-Fi. Decision Support System is applied in this study as a system for determining the location of public Wi-Fi installations. In determining the location of the right public Wi-Fi installation, it must meet criteria such as Distance, Accessibility, Economy, Crowd, and Facilities. Therefore, a Decision Support System (DSS) is needed in solving existing problems by applying the MABAC (Multi-Attributive Border Approximation area Comparison) method which can generate preference values from the first ranked alternative. So that the location for the installation of Public Wi-Fi is located on the A4 alternative, namely the Sultan Thaf Grand Mosque with a value of 0.480.